2018
DOI: 10.1186/s12933-018-0659-2
|View full text |Cite
|
Sign up to set email alerts
|

Increase in relative skeletal muscle mass over time and its inverse association with metabolic syndrome development: a 7-year retrospective cohort study

Abstract: BackgroundSkeletal muscle mass was negatively associated with metabolic syndrome prevalence in previous cross-sectional studies. The aim of this study was to investigate the impact of baseline skeletal muscle mass and changes in skeletal muscle mass over time on the development of metabolic syndrome in a large population-based 7-year cohort study.MethodsA total of 14,830 and 11,639 individuals who underwent health examinations at the Health Promotion Center at Samsung Medical Center, Seoul, Korea were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 54 publications
4
50
0
1
Order By: Relevance
“…For example, Asian populations have lower BMI values, but a higher risk of IR as well as a higher visceral fat level or fat percentage for a given BMI, than have Caucasians . Many studies have investigated the associations of skeletal muscle mass and FM or %BF with MetS in Asian populations . Muscle mass and strength are protective factors against cardiometabolic risk, whereas high FM index, %BF, and visceral obesity are each positively associated with MetS and IR .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Asian populations have lower BMI values, but a higher risk of IR as well as a higher visceral fat level or fat percentage for a given BMI, than have Caucasians . Many studies have investigated the associations of skeletal muscle mass and FM or %BF with MetS in Asian populations . Muscle mass and strength are protective factors against cardiometabolic risk, whereas high FM index, %BF, and visceral obesity are each positively associated with MetS and IR .…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors that have been associated with MetS were childhood retinol-binding protein 4 levels, independently of pediatric obesity [ 15 ], and fast eating speed, independently of total energy intake, body mass index at baseline, and body mass index change during the follow-up period [ 16 ]. On the other hand, an increase in relative skeletal muscle mass over time resulted to have a protective preventive effect on developing MetS [ 17 ]. Additionally, supervised high-intensity interval training has resulted to improve MetS and body composition in myocardial infarction patients with MetS undergoing cardiac rehabilitation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“… 5 Several studies have reported that sarcopenia and low muscle mass are risk factors for MetS. 6 – 8 The current consensus on the diagnosis of sarcopenia includes low muscle strength, low skeletal muscle mass, and/or low physical performance. Handgrip strength (HGS) correlates with total muscle strength and has been shown to predict many adverse outcomes including functional decline, falls, and mortality.…”
Section: Introductionmentioning
confidence: 99%